2000
DOI: 10.1093/jn/130.4.813
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Heat Exposure Alters Protein Turnover of Three Different Skeletal Muscles in Finishing Broiler Chickens Fed 20 or 25% Protein Diets

Abstract: Heat-exposed chickens exhibit a lower growth rate and a depressed protein retention which may result from an alteration in protein metabolism. A high-protein diet seems to be beneficial under hot conditions because it tends to improve growth. Effects of high ambient temperature (32 vs. 22°C) and dietary crude protein (25 vs. 20%) on muscle protein turnover were investigated in finishing broiler chickens. At 5-6 wk of age, protein synthesis was measured in vivo in the Pectoralis major, Sartorius and Gastrocnemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
1
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 22 publications
5
75
1
9
Order By: Relevance
“…Cheng et al (1999) relataram que diminuir a proteína bruta da dieta pode melhorar o desempenho das aves criadas em ambiente quente. No entanto, Alleman & Leclercq (1997) e Temim et al (2000) demonstraram que esse procedimento acentuou os efeitos prejudiciais do estresse por calor sobre o desempenho dos frangos de corte.…”
Section: Introductionunclassified
“…Cheng et al (1999) relataram que diminuir a proteína bruta da dieta pode melhorar o desempenho das aves criadas em ambiente quente. No entanto, Alleman & Leclercq (1997) e Temim et al (2000) demonstraram que esse procedimento acentuou os efeitos prejudiciais do estresse por calor sobre o desempenho dos frangos de corte.…”
Section: Introductionunclassified
“…Various nutritional strategies have been suggested to overcome the negative impact of heat stress in broilers. Especially recent researches have focused on dietary protein levels, and one other favorite way is adding antioxidants to the ration (Temim et al, 2000a;Temim et al, 2000b;Gonzalez-Esquerra & Leeson, 2006;Syafwan et al, 2011). Therefore, we have focused on; how antioxidants system affected from protein level and vitamin content, which has to be, organized to resolve or to minimize the negative effects of stress.…”
Section: The Effects Of Different Amount Of Protein and Vitamin E Supmentioning
confidence: 99%
“…Temim et al (2000a) carried out a research that animals fed with diets containing 19% and 24% protein, at 22 o C and 32 o C. In this study, Temim et al (2000a) found that heat stress adversely affects the conversion metabolism of proteins to the muscles, and increasing protein percentage of the diet partially prevented this negative effect.…”
Section: The Effects Of Different Amount Of Protein and Vitamin E Supmentioning
confidence: 99%
“…; Temim et al, 2000b;Faria Filho, 2003) These findings are associated with the different metabolism of each specific tissue: the breast present glycolytic metabolism, whereas the leg muscles present oxidative metabolism (Ain Baziz et al, 1996). The broilers exposed to heat stress on day 36 presented higher carcass fat content between 22 and 46 days of age compared with the broilers submitted to heat stress on day 25 and with those not exposed to heat stress.…”
mentioning
confidence: 99%